Venlafaxine Improves the Cognitive Impairment and Depression-Like Behaviors in a Cuprizone Mouse Model by Alleviating Demyelination and Neuroinflammation in the Brain - Zhang, Yanbo; Bi, Xiaoying; Adebiyi, Olubunmi; Wang, Junhui; Mooshekhian, Ali; Cohen, Jacob; Wei, Zelan; Wang, Fei; Li, Xin-Min (Frontiers in Pharmacology, 2019)
Growing evidence has implicated that myelin deficits and neuroinflammation may be a shared pathophysiology and treatment target for the mood and cognitive symptoms in major depressive disorder and multiple sclerosis. Venlafaxine is a versatile antidepressant for depression, anxiety and neuropathy. Previous studies showed venlafaxine has neuroprotective effects through multiple mechanisms. However, it is unclear whether venlafaxine treatment can alter myelin integrity and inflammation status in the brain. We investigated the effects of venlafaxine in an acute cuprizone mouse model of demyelination. This animal model exhibits cognitive impairment and mood disturbances, brain myelin loss and prominent neuroinflammation. This study was a two by three design with a total of six groups of C57BL/6 mice (n=16 per group). Three groups on regular diet received vehicle (water), venlafaxine 5mg/kg or 20 mg/kg daily for five weeks respectively; other three groups were fed with 0.2% cuprizone and concurrently received vehicle (water), venlafaxine 5mg/kg or 20 mg/kg daily for six weeks respectively. The working memory and depression-like behaviors were assessed using the Y-maze, tail suspension and forced swim tests. Mice brains were harvested after euthanasia and processed for immunohistochemistry of myelin pathology, oligodendrocyte, astrocyte and microglia. A high dose of venlafaxine treatment improved the working memory and depression-like behaviors, mitigated myelin and oligodendrocyte loss. The protective effect may be mediated by reducing microglia-medicated inflammation in the brain. These findings suggest that myelin integrity and neuroinflammation modulation may be part of the mechanisms behind venlafaxine’s therapeutic effects.